Exploring gendered perspectives of pastoralist communities on zoonotic risks through community conversations on human-animal interaction in cross-border areas of Ethiopia and Kenya - Lemma, Mamusha; Mumin, Farah I.; Assefa, A.; Fascendini, M.; Mor, Siobhan M. (CAB International, 2025)
Background: The cross-border areas of Ethiopia and Kenya are home to pastoralist communities that rely on livestock as a primary source of food and income, leading to frequent interaction between humans and animals and increasing the potential for exposure to health risks, including zoonotic diseases. Given limited access to healthcare in these areas, primary prevention efforts that raise individual and community awareness and promote sustained health behaviour change are paramount. Community conversations (CCs) are facilitated dialogues that engage community members in examining their perceptions and practices around a specific issue, while collaboratively identifying and developing solutions.